2008
DOI: 10.2486/indhealth.46.348
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Brain Levels of Neurotransmitters and Amino Acids in Male F344 Rats Induced by Three-week Repeated Inhalation Exposure to 1-Bromopropane

Abstract: The present study investigated the effects of 1-bromopropane (1BP) on brain neuroactive substances of rats to determine the extent of its toxicity to the central nervous system (CNS). We measured the changes in neurotransmitters (acetylcholine, catecholamine, serotonin and amino acids) and their metabolites or precursors in eight brain regions after inhalation exposure to 1BP at 50 to 1,000 ppm for 8 h per day for 7 d per week for 3 wk. Rats were sacrificed at 2 h (Case 1), or at 19 h (Case 2) after the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
4
1
1
Order By: Relevance
“…Previous studies have shown that 1-BP exposure enhances neuronal excitability in the hippocampus through the over-activation of NMDARs [23,46]. Consistent with previous reports, we found that the concentrations of GABA and Tau were significantly decreased in 1-BP-intoxicated rats [47]. Meanwhile, 1-BP intoxication increased the levels of excitatory Asp in rats, although the levels of Glu remained unchanged.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that 1-BP exposure enhances neuronal excitability in the hippocampus through the over-activation of NMDARs [23,46]. Consistent with previous reports, we found that the concentrations of GABA and Tau were significantly decreased in 1-BP-intoxicated rats [47]. Meanwhile, 1-BP intoxication increased the levels of excitatory Asp in rats, although the levels of Glu remained unchanged.…”
Section: Discussionsupporting
confidence: 91%
“…1). In addition, these hallmarks of hypothalamic concentrations were consistent with previously reported biochemical values in rats (17) and mice (18,19), in particular the high GABA and low Glu concentrations, which could point to GABA as a dominant neurotransmitter in hypothalamus (20). Furthermore, the observed increased hypothalamic choline content mostly in the form of GPC was in excellent agreement with chromatographic measurements in mice (21).…”
Section: Discussionsupporting
confidence: 91%
“…Relative to CO, ST and HI, Gly in MO showed a three‐fold higher concentration (Fig. 3a), which is in accordance with the reported Gly regional distribution in rat brain 20, 22. The high concentration of Gly in MO is consistent with its neurotransmitter function in this region.…”
Section: Discussionsupporting
confidence: 88%
“…1). An excellent agreement of the concentrations of Glu, Gln, GABA and Tau in MO was found with previously quantified values in tissue extracts 20.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation